Isolation, Characterization and Pathogenicity of Edwardsiella tarda a Causative Disease on Freshwater Fish in Yogyakarta - Murwantoko Murwantoko; Eka Diniarti; Triyanto Triyanto (Universitas Gadjah Mada, 2019)
Edwarsiella tarda is a cosmopolitan bacterium and is a cause of Edwardsiellosis in various fish species. The bacterial infection causes large losses on aquaculture in Asia, especially Japan. This study was conducted to isolate and characterize E. tarda as causative disease in freshwater fishes, and to determine its pathogenicity to catfish (Pangasius sp.). Bacteria were isolated from kidney of diseased fishes on Tryptone Soya Agar medium. Identification was conducted based on morphological colonies, morphological cells and biochemical tests. Fulfillment of Koch Postulates was done by injecting bacteria intraperitoneally on 7-9 cm fishes at dose of 107 cfu/fish. Pathogenicity test was carried out by intraperitoneal injection at 104, 105, 106, and 107 cfu/fish to 7-9 cm-catfish (Pangasius sp.) and followed by observation of disease signs and mortality every six hours for 7 days. Pathogenicity was determined as Lethal Dosage (LD50) using Dragstedt Behrens method. In this research we have isolated three isolates E. tarda causing disease in fishes. The clinical signs of this disease were lose of pigmentation over the lession, swollen of stomach, haemorhage on fins , small cutaneous lesions, and necrotic on fins area. The LD50 of E. tarda isolate L2, L3, and N3 were 4.64 ± 0.35x105, 1.54 ± 0.07x105, and 1.13 ± 0.13x106 cfu/fish, respectively.